Antimicrobial Resistance Profiles of Non-typhoidal Salmonella From Retail Meat Products in California, 2018 - Lee, Katie Yen; Atwill, Edward Robert; Pitesky, Maurice; Huang, Anny; Lavelle, Kurtis; Rickard, Maribel; Shafii, Marzieh; Hung-Fan, Melody; Li, Xunde (Frontiers in Microbiology, 2022)
Non-typhoidal Salmonella remains a leading cause of foodborne illness in the United States, with food animal products serving as a key conduit for transmission. The emergence of antimicrobial resistance (AMR) poses an additional public health concern warranting better understanding of its epidemiology. In this study, 958 retail meat samples collected from January to December 2018 in California were tested for Salmonella. From multivariable logistic regression, there was a 6.47 (90% CI 2.29–18.27), 3.81 (90% CI 1.29–11.27), and 3.12 (90% CI 1.03–9.45) higher odds of contamination in samples purchased in the fall, spring, and summer than in winter months, respectively, and a 3.70 (90% CI 1.05–13.07) higher odds in ground turkey compared to pork samples. Fourteen distinct serotypes and 17 multilocus sequence types were identified amongst the 43 isolates recovered, with S. Kentucky (25.58%), S. Reading (20.93%), S. Typhimurium (9.30%), and S. Infantis (9.30%) comprising the top serotypes. High prevalence of resistance was observed in retail chicken isolates for streptomycin (12/23, 52.17%) and tetracycline (12/23, 52.20%), in ground turkey isolates for ampicillin (8/15, 53.34%), and in ground beef isolates for nalidixic acid (2/3, 66.67%). Fourteen (32.56%) were susceptible to all antimicrobials tested, 11 (25.58%) were resistant to one drug, and 12 (27.91%) were resistant to two drugs. The remaining six isolates (13.95%) were multidrug-resistant (≥3 drug classes) S. Infantis (n=3), S. Reading (n=2), and S. Kentucky (n=1). Whole-genome sequencing (WGS) identified 16 AMR genes and 17 plasmid replicons, including blaCTX-M-65 encoding ceftriaxone resistance and a D87Y mutation in gyrA conferring resistance to nalidixic acid and reduced susceptibility to ciprofloxacin. The IncFIB(pN55391) replicon previously identified in connection to the worldwide dissemination of pESI-like mega plasmid carriage in an emerged S. Infantis clone was detected in 4 of the 6 MDR isolates. Genotypes from WGS showed high concordance with phenotype with overall sensitivity and specificity of 95.31% and 100%, respectively. This study provides insight into the AMR profiles of a diversity of Salmonella serotypes isolated from retail meat products in California and highlights the value of routine retail food surveillance for the detection and characterization of AMR in foodborne pathogens.